Social insurance and allied services : memorandum on the Beveridge Report
1943-02-10 1943 1940s 24 pages BRITISH EMPLOYERS' CONFEDERATION. SOCIAL INSURANCE AND ALLIED SERVICES. Memorandum on the "Beveridge" Report. I. INTRODUCTORY: (1) Sir William Beveridge's Report on Social Insurance and Allied Services consists really of two parts: (a) a comprehensive Survey of the history and present position of all these Services; and (b) Sir William's own Recommendations for a new comprehensive system. (2) The Survey is a monumental piece of work. It embodies the combined knowledge and experience of Sir William and the expert representatives of all the Government Departments concerned and thus provides the essential groundwork for designing the reconstruction policy of this country so far as these vitally important Services are concerned. This is the first time the country has had a comprehensive picture of these Services. Throughout the past twenty years the Confederation, in its evidence before the various Government Commissions and Committees which have examined the Insurance Services in watertight compartments, has consistently urged the necessity for such a comprehensive review. The Confederation therefore, in welcoming this Survey, would wish to pay tribute to the great national service which Sir William and his Government colleagues have done in preparing it. (3) The Recommendations in the Report, on the other hand, are those of Sir William alone. The Departmental Committee with Sir William Beveridge as its Chairman was set up in June, 1941, but the Report when issued explained that in January, 1942 the Government, recognising that issues of high policy would arise in the Report, had decided that Sir William's colleagues on the Committee would "not be associated in any way with the views and recommendations on questions of policy" which the Report might contain. (4) The Report as a whole therefore is the Report of only one man. At the same time, there is no one in the country who knows more about the technique of this subject than Sir William, and the country must be grateful to him for not only having designed a scheme, but also for having presented it in a realistic/ 200/B/3/2/C216/5/50